INSTITUCIONALIZAÇÃO DE INOVAÇÕES ORGANIZACIONAIS EM UMA EMPRESA DE SANEAMENTO - Baldissera, Deborah Stocco Machado (2020)
Organizations need to constantly innovate to remain in business, with the objective of achieving competitive advantages and higher profitability. This innovation must be sustainable and aimed for the long term; what is innovation today, will not be tomorrow. In this sense, there is the need of organization to develop factors that approach Innovation Capability (IC), which will generate Organizational Innovation (OI), in order that innovation is part of the routine of the organization, i.e., to be sedimented in its structure. Therefore, this research is based on Innovation Capability Theory (IC) and on Institutional Theory (IT). With IC, organizations can manage different capabilities and key organizational resources that promote innovation activities. On the other hand, IT states that organizations are similar in seeking legitimacy in business. Thus, these theories use isomorphism mechanisms, whether they are regulatory, normative or cognitive, and go through the institutionalization process, which will lead to the sedimentation of innovations in the organization. In this context, this research is carried out in a Sanitation Company located in the South of Brazil, here fictitiously called COMSUL, which has been in business for over 55 years, being a governmentcontrolled business corporation. Therefore, this dissertation brings the following question: how do organizational innovations are institutionalized in COMSUL? To answer this inquiry, the research aims to discuss the institutionalization of organizational innovations in COMSUL. Thus, it is a qualitative research, classified as an exploratory-descriptive case study, in which interviews were used as the main source of data collection, as well as the systematic observation, field diary and the Company's document. Content analysis was used with the help of Atlas Ti® software - CAQDAS (computer assisted qualitative data analysis software) for the categorization and data analysis. As results, aspects of 20 COMSUL innovations were described. Such innovations were classified within the stages of institutionalization, being 05 in the stage of habitualization, 10 in objectification and 05 totally sedimented (the OIs within the Company are in the objectification stage). This is justified because COMSUL has been committed to promoting innovation internally, always trying to adapt, reconfiguring itself in response to internal and, especially, external factors. It has also been identified that OIs happen in a strategic way, being more relevant than all other types of innovations, because they assemble and stimulate all other innovations. Furthermore, it was found that at different organizational levels there are different perceptions of innovation; innovation is permeating the structure, however in an unplanned manner, and innovation management is centralized in the Research and Innovation Management. Regarding the institutionalization, COMSUL innovates mostly in response to the regulatory pillar, based on laws, regulatory or supervisory entities, but there are also influences of the regulatory pillar, such as the search for certifications and, to a lesser extent, the cognitive pillar. The results highlight that the Company must be aware of innovations that are not sedimented, however, within the parameters set forth in this study, it can be considered innovative and is on the right direction.